The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1186/s40729-020-00227-5
|View full text |Cite
|
Sign up to set email alerts
|

The lack of keratinized mucosa is associated with poor peri-implant tissue health: a cross-sectional study

Abstract: Objectives The aim of this cross-sectional study is to determine the association between the absence of keratinized mucosa and peri-implant tissue health. Methods and materials This cross-sectional study comprised 412 implants from 200 patients from faculty-based clinics. Demographic, medical, and clinical information were collected. The modified sulcus bleeding index, modified plaque index, mucosal recession, probing depth, bone level, the width of keratinized mucosa, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 40 publications
0
44
0
1
Order By: Relevance
“…Many studies have focused on the relationship between the width of keratinized tissue (KT) and peri-implant health. Several reports have presented associations between improved esthetic results, peri-implant health, implant survival, and adequate KT width [ 1 2 3 ]. However, other reports have found that there were minimal or no associations among involution of the peri-implant tissue, implant survival, and the width of KT [ 4 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have focused on the relationship between the width of keratinized tissue (KT) and peri-implant health. Several reports have presented associations between improved esthetic results, peri-implant health, implant survival, and adequate KT width [ 1 2 3 ]. However, other reports have found that there were minimal or no associations among involution of the peri-implant tissue, implant survival, and the width of KT [ 4 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, dental implants are wrapped annularly by connective tissue, relying only on hemidesmosome connections[ 6 ]. Peri-implant gingiva is so easy to move, thereby causing peri-implantitis that is attributed to bacterial invasion[ 7 ]. From another perspective, the attached gingiva of healthy teeth is composed of keratinized gingiva.…”
Section: Discussionmentioning
confidence: 99%
“…Recesijų atsiradimas aplink dantų implantus turi neigiamos įtakos estetikai ir kokybiškai individualiai burnos higienai. Dauguma naujausių tyrimų nurodo nepakankamo KDP įtaką recesijų atsiradimui [9,19,21,22,28,33]. Naujausi bent 5 metų trukmės kokybiniai tyrimai apibendrinti V. Iorio-Siciliano ir bendraautorių [34] sisteminėje apžvalgoje, kurioje aprašytos dvi studijos, kai didesnės recesijos atsirado esant <2 mm KDP.…”
Section: Tyrimo Rezultatai Ir Jų Aptarimas Keratinizuotų Dantenų Plotis Ir Jo Klinikinė Reikšmėunclassified